1992
DOI: 10.1271/bbb.56.853
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Novel Extracellular Polysaccharide by aBacillusStrain Isolated from Soil

Abstract: A bacterium that was isolated from soil and identified as Bacillus circulans was found to produce a highly viscous extracellular polysaccharide when it was grown aerobically in a medium containing glucose as a sole source of carbon. The product was characterized by TLC and GC analyses as a novel heteropolysaccharide consisted of rhamnose, mannose, galactose, and mannuronic acid as sugar components. A maximal yield of polysaccharide reached about 2 g/liter by jar-fermentor culture at 30°C for 48 hr with a mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…A jar-fermentor (MSJ-30, Marubishi B.E. Co., Ltd., Tokyo) culture was performed at 30'C for 48 h with 10 1 of the medium by inoculating I / of a preculture, which was cultured as described in the previous paper (Kawai et a/., 1992), with an aeration rate at 1.5 / per minute and an agitation speed at 300 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A jar-fermentor (MSJ-30, Marubishi B.E. Co., Ltd., Tokyo) culture was performed at 30'C for 48 h with 10 1 of the medium by inoculating I / of a preculture, which was cultured as described in the previous paper (Kawai et a/., 1992), with an aeration rate at 1.5 / per minute and an agitation speed at 300 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the culture conditions of the bacterium for the production of polysaccharide (Kawai et a/., 1992), and the physicochemical properties ofthe bacterial polysaccharide (BPS) were examined to apply it to the food industry as raw materials (Isobe et a/., 1996).…”
mentioning
confidence: 99%
“…O maior crescimento e a maior produção de polissacarídeo ocorrem na faixa de 25-35ºC, onde cada espécie bacteriana apresenta a sua temperatura ótima (GANDHI; RAY; PATEL, 1997;KAWAI et al, 1992;VERMANI;KELKAR;KAMAT, 1995).…”
Section: Parâmetros Envolvidos No Processo De Produção Dos Polissacarunclassified
“…1) We attempted to analyze the molar ratio of those sugar components except for mannuronic acid after separation by thin-layer chromatography as described in Materials and Methods. It was found that the molar ratio of D-galactose: D- mannose: L-rhamnose was 1.3: 1 : 2, indicating that the polysaccharide consisted mainly of D-rhamnose as sugar components.…”
Section: Molar Ratio Of Sugar Components Of Polysaccharidementioning
confidence: 99%
“…In our previous paper, 1) we reported that a soil bacterium that was identified as Bacillus circulans produced a highly viscous water-soluble polysaccharide when it was grown aerobically in a medium containing glucose, yeast extract, asparagine, and inorganic salts. It was also found that the polysaccharide consisted of L-rhamnose, D-galactose, Dmannose, and D-mannuronic acid as sugar components, from which we considered that it might be a novel polysaccharide produced by the same species of bacteria.…”
mentioning
confidence: 99%